Dust potency in the context of solar photovoltaic (PV) soiling loss. (15th May 2021) - Javed, Wasim; Guo, Bing; Figgis, Benjamin; Aïssa, Brahim
Highlights: PV soiling loss can be seen as a function of dust accumulation mass and dust potency. Dust potency, soiling loss per unit area dust mass, ranges 2–8% g −1 m 2 worldwide. Dust potency in Qatar varies seasonally, lowest in the mid-year dry, windy months. Dust potency variation correlates with chemical composition and particle size. A simple model for PV soiling loss prediction as a function of dust mass and dust potency is evaluated. Abstract: We report on the impact of natural soiling on PV module performance loss in terms of dust potency (i.e., soiling loss per unit area dust mass) affected by dust composition and environmental conditions. Samples of accumulated dust mass (ADM) on PV panels from Doha, Qatar, were collected at different periods over two years. Our analysis demonstrated that dust accumulation rate and dust potency exhibited seasonal patterns influenced by environmental conditions. The measured dust potency varied significantly from month to month, ranging from 2 to 3.7% g −1 m 2 that situates in the range of 2 – 8% g −1 m 2 found in the literature. The lower dust potency was observed during the summer months, characterized by strong winds and low humidity. Soiling loss may be seen as a function of ADM and the dust potency, with the latter being a function of dust physico-chemical properties. ADM also has a significant seasonal fluctuation both in terms of particle size distribution and chemical composition. The dust potency is found to be impacted by the particle size, elemental carbon (EC), organic carbon (OC), and ions contents of the dust. ADM with lower dust potency has shown larger size particles and low EC/OC contents, while the effect of soluble ions on dust potency is found to be complex, due most probably to the interactions with humidity. Finally, based on the experimental and literature data, we developed a practical and straightforward model to estimate PV soiling loss as a function of dust mass and dust potency.